PENGARUH KOMITE AUDIT, AUDIT DELAY, DAN AUDIT FEE TERHADAP AUDITOR SWITCHING - Sarah Monica, (2022)
The purpose of this study is to examine the effect of the audit committee, audit delay, and audit fee on auditor switching. Purposive sampling is the procedure utilized to acquire samples. With a total sample of 220 data, this study included 44 companies in consumer non-cylicals sector that were listed on the Indonesia Stock Exchange (IDX) in 2016 - 2020. The data analysis technique used is logistic regression analysis with a 5% significance level and data testing with SPSS software. According to the findings of this study, (1) audit committee has no effect on auditor switching; (2) audit delay has no effect on auditor switching; and (3) audit fee has a significant negative effect on auditor switching.